Exploring the line between the preventive and punitive character of measures in the frame of a just culture. Issue 2 (3rd July 2017) - Karanikas, Nektarios; Chionis, Dimitrios
Abstract: This paper presents the results of a survey which aimed at exploring the perceptions of the employees of a large aviation organization regarding the punitive or preventive character of possible measures that management could take in cases of errors and violations. The analysis of the quantitative and qualitative data collected showed that the viewpoints of the staff were sufficiently aligned only for half of the measures and that all measures inflicting a short- or long-term dissociation of the end-users from their current working place and function were highly unfavourable and linked to castigation. Also, statistically significant differences were observed across groups of specialties and years of service regarding the appropriateness of specific measures especially in the case of errors. The findings of this study in combination with literature references, suggest that the establishment of a just culture structure with agreed lines between the punitive and preventive character of measures and its endorsement by the employees is achievable, but it requires a bottom-up approach and periodical revision. Similar exploratory research, complemented possibly by explanatory studies, is recommended to be carried out by organizations prior or during the development of their just culture policy and related measures.